2016
DOI: 10.4236/cs.2016.79231
|View full text |Cite
|
Sign up to set email alerts
|

Cross Layered MAC Design for RF Energy Harvesting Sensor Network

Abstract: The main research objective in wireless sensor networks (WSN) domain is to develop algorithms and protocols to ensure minimal energy consumption with maximum network lifetime. In this paper, we propose a novel design for energy harvesting sensor node and cross-layered MAC protocol using three adjacent layers (Physical, MAC and Network) to economize energy for WSN. The basic idea behind our protocol is to re-energize the neighboring nodes using the radio frequency (RF) energy transmitted by the active nodes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…A MAC/Routing cross-layer protocol for wireless sensor nodes with RF energy-harvesting capabilities is proposed in Sasikala and Kumar (2016). The sensor nodes toggle between transceiver mode or harvesting mode based on the energy-harvesting time and the node's active time.…”
Section: Cross-layer Protocolsmentioning
confidence: 99%
“…A MAC/Routing cross-layer protocol for wireless sensor nodes with RF energy-harvesting capabilities is proposed in Sasikala and Kumar (2016). The sensor nodes toggle between transceiver mode or harvesting mode based on the energy-harvesting time and the node's active time.…”
Section: Cross-layer Protocolsmentioning
confidence: 99%
“…The Cross-Layer MAC Energy Harvesting Sensor Node (CL_EHSN) [ 179 ] is another protocol that belongs to this group. In the CL_EHSN protocol, first of all, a path is established between two nodes with the help of routing protocols.…”
Section: Energy Harvesting Mac Protocolsmentioning
confidence: 99%
“…The authors demonstrated that their proposed algorithm reduces 42% of the Central Processing Unit-memory (CPU-memory) related energy consumption. Besides, in the CL_EHSN cross-layer mechanism [ 179 ], which is explained in Section 6 , the processor-memory related power consumption can be reduced through the energy-aware MAC, which makes the decisions based on the status of the battery, and estimating the charging time. The implementation complexity of the MAC protocol, or its algorithms, is another issue that consumes some parts of the network energy consumption.…”
Section: Open Issues and Research Challenges For Energy Harvesting Mac Protocols Within Iot Systemsmentioning
confidence: 99%
See 1 more Smart Citation